Sistem Monitoring Kualitas Udara Jarak Jauh Berbasis Sensor MQ-2, MQ-6 dan Sensor DHT11 - Iqbal, Muhammad; Puspita, Nabilla Putri; Rasyid, Rahmad; Yusfi, Meqorry (Universitas Andalas, 2025)
Air quality is influenced by activities that produce gas from natural and human sources, so monitoring gas levels is important to prevent health threats. The goal is to create a natural gas monitoring tool that is efficient (easy to use) and can be accessed from a smartphone. The tool designed uses MQ-2 and MQ-6 sensors for detecting gas levels and DHT11 sensors for temperature and humidity. Data is sent in real-time on the smartphone via the Blynk application with the nRF24L01+ module. The results showed that the system worked well in monitoring butane, methane, temperature, and humidity. The highest error value on the MQ-2 sensor is 24.375%. Methane gas measurements using the MQ-6 sensor show the highest error value of 11.06%. The nRF24L01+ module successfully sends data to the receiver and activates the Light Emitting Diode (LED) and buzzer when the value exceeds the set limit. This module can send data up to a distance of 1000 meters without Line-of-Sight (LOS) obstructions and has a reduced distance of up to 600 meters in the presence of Non-Line-of-Sight (NLOS) obstructions. The Blynk application successfully displays data measuring gas levels, temperature and humidity.